Rationale and design of EXPLORE: a randomized, prospective, multicenter trial investigating the impact of recanalization of a chronic total occlusion on left ventricular function in patients after primary percutaneous coronary intervention for acute ST-elevation myocardial infarction - Tuseth Vegard (Trials, 2010)
Abstract Background In the setting of primary percutaneous coronary intervention, patients with a chronic total occlusion in a non-infarct related artery were recently identified as a high-risk subgroup. It is unclear whether ST-elevation myocardial infarction patients with a chronic total occlusion in a non-infarct related artery should undergo additional percutaneous coronary intervention of the chronic total occlusion on top of optimal medical therapy shortly after primary percutaneous coronary intervention. Possible beneficial effects include reduction in adverse left ventricular remodeling and preservation of global left ventricular function and improved clinical outcome during future coronary events. Methods/Design The Evaluating Xience V and left ventricular function in Percutaneous coronary intervention on occLusiOns afteR ST-Elevation myocardial infarction (EXPLORE) trial is a randomized, prospective, multicenter, two-arm trial with blinded evaluation of endpoints. Three hundred patients after primary percutaneous coronary intervention for ST-elevation myocardial infarction with a chronic total occlusion in a non-infarct related artery are randomized to either elective percutaneous coronary intervention of the chronic total occlusion within seven days or standard medical treatment. When assigned to the invasive arm, an everolimus-eluting coronary stent is used. Primary endpoints are left ventricular ejection fraction and left ventricular end-diastolic volume assessed by cardiac Magnetic Resonance Imaging at four months. Clinical follow-up will continue until five years. Discussion The ongoing EXPLORE trial is the first randomized clinical trial powered to investigate whether recanalization of a chronic total occlusion in a non-infarct related artery after primary percutaneous coronary intervention for ST-elevation myocardial infarction results in a better preserved residual left ventricular ejection fraction, reduced end-diastolic volume and enhanced clinical outcome. Trial registration trialregister.nl NTR1108.